Comparison between adrenalectomy and medical therapy in the management of primary aldosteronism - Loh, Huai Heng; S, Norlela; AW, Norasyikin; M, Norlaila; Zainuddin, Suehazlyn; R, Subashini; O, Mohd Rahman; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; WS, Wan Juani; D, Azura; OOI, CP; et al. (Malaysian Endocrine and Metabolic Society, 2014)
Introduction: Primary aldosteronism (PA) is a disorder of the adrenal gland causing an autonomous overproduction of mineralocorticoids, leading to arterial hypertension. Objective: To assess outcome between adrenalectomy and the use of mineralocorticoid receptor antagonist (MRA) in primary aldosteronism. Materials and Methods Registry of all patients with treated PA referred to our center from 2001 till 2013 were reviewed. Demographics of the patients and outcome one year after treatment were analysed. Results: There were 12 female and 10 male patients. Mean age was 49.23 ± 11.3. Median duration of hypertension prior to diagnosis of PA was 7.5 ± 8.3 years. Median aldosterone renin ratio was 53.2 (aldosterone in ng/ dL, renin in ng/ml/h). 82% had fludrocortisone suppression as confirmatory test. 45.5% underwent adrenalectomy, 36.4% received MRA, with mean dose of 75mg/day. Mean potassium level pre-treatment was 2.75 ± 0.72mmol/L, with post level of 4.35 ± 0.43mmol/L. In the adrenalectomy arm, there was significant improvement in SBP (p=0.001) and potassium level (p<0.001) post treatment. In the MRA arm, there was significant improvement in SBP (p=0.001), DBP (p=0.001) and potassium level (p=0.002). Post adrenalectomy patients required less anti-hypertensive treatment compared to patients who received MRA (p=0.039). There was no significant difference in blood pressure improvement (p=0.43 for SBP, p=0.13 for DBP) and potassium improvement (p=0.58) between two modalities of treatment. Conclusion: Both adrenalectomy and medical therapy resulted in significant improvement in both blood pressure and potassium level. Due to the small number of subjects, only reduction of anti-hypertensive treatment heralds the superiority of surgery over medical treatment in this study.